EMOSI POSITIF MANUSIA PERSPEKTIF AL-QUR’AN DAN APLIKASINYA DALAM PENDIDIKAN - Miftah Ulya (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2019)
Abstract: Humans are unique creatures that have emotions. The emotions behind the actions and willingness are also closely intertwined with all the personalities that give color to the mood. Emotion is a biological and psychological state and a series of tendencies to act that exist in oneself almost in every human action. In the Qur'an, the phrase "human emotion" is directly related to human behavior, both as individual beings (fardiyah) and social (jama ’iyah), both in the aspects of the past, present, and future information. In general, described pleasant emotional expressions, and there are also unpleasant emotional expressions. In al-Quran there are many explanations and descriptions of various basic emotions felt by humans. Fear, happy or happy, and other emotions. In the midst of the hustle and bustle of emotional problems that do not escape the process of transfer of knowledge in the realm of education that can affect the exemplary crisis as a figure in education, then by putting positive emotions as a basic reference, it will be felt as a solution that can provide one-one solutions to the world education today. Keynote: Emotions, al-Qur'an, Application, Education.